Effect of in-hospital nurse-led smoking cessation intervention for patients with atherosclerotic cardiovascular disease: a randomised pilot study. (3rd October 2022) - Pleym, K; Sverre, E; Weedon-Fekjaer, H; Kahlon, M; Husebye, E; Tonstad, S; Dammen, T; Munkhaugen, J
Abstract: Background: Smoking remains prevalent after cardiovascular disease (CVD) events and knowledge on how to facilitate effective cessation in clinical practice is needed. Purpose: To test the effect of an in-hospital nurse-led intervention on the participation rate at municipal Healthy Life Centres (HLC) and the use of smoking cessation drugs. Secondary, to determine long-term effects on cessation rates. Methods: A prospective, randomized, open-label, parallel-group intervention pilot-study was conducted at a Norwegian secondary care hospital in 2021. Patients with atherosclerotic CVD who smoked at least one cigarette daily when admitted with an acute CVD event were consecutively included. The nurse-led intervention included cessation counselling utilizing motivational interview technique, information and guidance in proper use of cessation drugs and direct referral to a 12-weeks digital (video ± phone) HLC program where patients received free cessation drugs. The low-threshold intervention included written information about the offer in the HLC with free cessation drugs. The primary endpoints were between-group differences in attendance rates at the HLC program and the use of cessation drugs. Results: Of 99 potential participants, 24 did not meet the entry criteria whereas 17 declined to participate. Of 58 randomised patients, three died during follow-up and 55 completed the study. Mean age was 65.7 (SD 9.2) years, 35% were female, 88% had low education, 88% had smoked >20 years, and motivation for quitting smoking was high (mean 8.5 on a 0 [no motivation] to 10 [high motivation] Likert scale). Comorbidity was common (mean Charlson score 5.1) and 40% had symptoms of anxiety and/or depression. The nurse-led intervention resulted in significantly higher participation rate at the HLC (48% vs. 4%, difference: 44% [95% CI: 24%, 65%], P<0.0001) and more frequent use of cessation drugs (48% vs. 11%, difference: 37% [95% CI: 15%, 60%], P=0.002) compared to the low-threshold intervention (Figure A). All participants in the intervention group who attended the HLC program were offered follow-up within 21 days following randomisation. In the intervention group 15% used varenicline and 33% used a combination of short and long-acting nicotine replacements. Clinically significant differences in cessation rates after six months were observed between the groups (Figure B). Concomitant carbon monoxide measurements were obtained of 5 participants in the intervention group and 4 in the control group who reported cessation and all confirmed non-smoking. Conclusion: Among multi-morbid patients hospitalised for a CVD event, a nurse-led intervention resulted in substantially higher participation rate at a municipal HLC program and higher use of smoking cessation drugs compared to written information. We also found clinically significant long-term effects on cessation rates which needs to be confirmed in a large-scale study. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Dam Foundation